Maintenance therapy for pediatric patients with high-risk Rhabdomyosarcoma: A report of dose reductions and dose omissions on outcome - Daniela Di Carlo; Lisa Lyngsie Hjalgrim; Beatrice Coppadoro; Michela Casanova; Andrea Ferrari; Véronique Minard-Colin; Hans Merks; Gianni Bisogno (EJC Paediatric Oncology)
Introduction: In the multicenter, open-label, randomized, controlled, phase 3 trial RMS2005, maintenance chemotherapy (MC), defined as vinorelbine (VNL) and low-dose cyclophosphamide (CPM), has been tested in high-risk patients affected by Rhabdomyosarcoma (RMS). The trial's results have shown that adding MC to 9 blocks of standard chemotherapy and surgery/radiotherapy improved overall survival. Following these results, MC has been incorporated into the standard of care for high-risk RMS patients. Drug doses were empirically titrated to avoid severe myelosuppression.Aspects like treatment adherence and drug doses effectively administered may have an important impact on the survival results and deserve to be studied. Methods: We analyzed 171 patients included in the RMS2005 protocol who received MC to quantify the deviation from the indications in terms of duration of maintenance and received doses and study its impact on survival. Results: Considering both drugs, 101/169 (60 %) of patients received a delivered cumulative dose (DCD) of at least 80 % of the planned cumulative dose, with a median DCD of 83 % (IQR 71–96).The median VNL and CPM relative dose intensity (RDI) was 0.88 (IQR 0.68–1).When the DCD or RDI for VNL, CPM and VNL plus CPM are included in the univariate and multivariate Cox model, as continuous or categorical variables, the effect is not significant both on the risk of developing events or death. Conclusion: The presented data about maintenance therapy suggested that dose modifications (as we registered them) did not affect event-free and overall survival.